Seroprevalence of Antibodies to Chlamydophila psittaci in Zoo Workers in Brazil - Raso, T.F; Carrasco, A.O.T; Silva, J.C.R; Marvulo, M.F.V; Pinto, A.A (Zoonoses and public health, 2010)
To evaluate the prevalence of antibodies to Chlamydophila psittaci 364 serum samples were collected from veterinarians, biologists, animal scientists, veterinary students, animal keepers and others employees in 20 zoos, and from veterinary practitioners in 10 Brazilian states. Subjects ranged from 15 to 64 years of age, with 268 (74%) males and 96 (26%) females. Chlamydial antibodies were determined by the complement fixation test (CFT) and specific anti-C. psittaci IgG antibodies were determined by the microimmunoflurescence (MIF) test. Complement fixation test showed 23.9% (87/364) and MIF test showed 4.7% (17/364) positive serum samples. Titres ranged from 16 to 256 in both assays, demonstrating evidence of recent or current infection. Although chlamydial antibodies were detected in workers of seventeen zoos, MIF test only detected specific C. psittaci antibodies in seven of them. Previous psittacosis infection was suspected in eight workers of two zoos, five of whom reported having pneumonia, while employed at the zoos. However, diagnosis was not established in any of these cases in the past. Results indicated the occurrence of infection and previous contact of Brazilian zoo workers with C. psittaci, as well as the zoonotic potential of psittacosis in this risk population. Other studies are necessary to evaluate the risk factors of infection in this population. This seroepidemiological survey confirmed the need to adopt preventive measures to control avian chlamydiosis and protect the health of zoo workers in the country.